Distributed Control Algorithm for Leader-Follower Formation Tracking of Multiple Quadrotors: Theory and Experiment - Wang, Zixuan; Zou, Yao; Liu, Yuzhen; Meng, Ziyang (IEEE/ASME transactions on mechatronics, 2021)
This article studies the leader-follower formation tracking problem of multiple quadrotors. In particular, the quadrotors are steered to track a reference trajectory while maintaining a desired configuration. The reference trajectory is partially available to a subset of quadrotors, and each quadrotor just interacts locally with its neighbors. A distributed control algorithm is proposed under a hierarchical framework. First, by introducing a distributed saturation control strategy, a command force is synthesized for the position to track the reference trajectory with a desired displacement. Second, a bounded applied force and a nonsingular command attitude are extracted from the synthesized command force based on a proper choice criterion of control parameters. Last but not the least, an applied torque is designed for the attitude to track the command one. In terms of Lyapunov theory, it is shown that the overall closed-loop error system is asymptotically stable. This indicates the accomplishment of the concerned leader-follower formation tracking control objective of multiple quadrotors. Finally, the effectiveness of the proposed distributed control algorithm is verified through both simulations and experiments.